The basic liberties: An essay on analytical specification. (July 2023) - McLeod, Stephen K; Tanyi, Attila
We characterize, more precisely than before, what Rawls calls the 'analytical' method of drawing up a list of basic liberties. This method employs one or more general conditions that, under any just social order whatever, putative entitlements must meet for them to be among the basic liberties encompassed, within some just social order, by Rawls's first principle of justice (i.e. the liberty principle). We argue that the general conditions that feature in Rawls's own account of the analytical method, which employ the notion of necessity, are too stringent. They ultimately fail to deliver as basic certain particular liberties that should be encompassed within any fully adequate scheme of liberties. To address this under-generation problem, we provide an amended general condition. This replaces Rawls's necessity condition with a probabilistic condition and it appeals to the standard liberal prohibition on arbitrary coercion by the state. We defend our new approach both as apt to feature in applications of the analytical method and as adequately grounded in justice as fairness as Rawls articulates the theory's fundamental ideas.